1989
DOI: 10.1128/aac.33.10.1686
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of ofloxacin in serum and cerebrospinal fluid of patients without meningitis receiving the drug intravenously and orally

Abstract: The cerebrospinal fluid (CSF) penetration of ofloxacin given orally or intravenously was studied in cancer patients without meningitis. Each patient was assigned to a different sampling time to assess the relation between time and penetration. Ofloxacin was measured in serum and CSF by high-pressure liquid chromatography and bioassay. In addition, the bactericidal titers were measured in CSF and serum against a set of relevant bacteria. Concentrations measured by high-pressure liquid chromatography and bioassa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
1

Year Published

1991
1991
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…A nonlinear plasma-CSF transit dependent on the concentration of drug in plasma has been observed with ciprofloxacin in rats, which may have been caused by a carrier-mediated transport from CSF to blood (8). In contrast, the CSF ofloxacin concentrations measured in the present study were approximately twofold greater than those found after administration of the first dose of 200 mg to subjects with uninflamed meninges (2,20); i.e., at doses of 200 and 400 mg, passage from serum to CSF was approximately linear in humans.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…A nonlinear plasma-CSF transit dependent on the concentration of drug in plasma has been observed with ciprofloxacin in rats, which may have been caused by a carrier-mediated transport from CSF to blood (8). In contrast, the CSF ofloxacin concentrations measured in the present study were approximately twofold greater than those found after administration of the first dose of 200 mg to subjects with uninflamed meninges (2,20); i.e., at doses of 200 and 400 mg, passage from serum to CSF was approximately linear in humans.…”
Section: Discussioncontrasting
confidence: 50%
“…dose of 200 mg (2,15,20,21). The concentrations in CSF were, however, not high enough to be relied upon for use in treating central nervous system (CNS) infections caused by the staphylococci predominantly involved in ventriculitis (2,15,20,21 Table 1). Patients with CNS infections or impaired renal function (creatinine level in serum, >1.2 mg/dl) were not included.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…or p.o., to volunteers or patients with normal renal function (1,5). Previous studies have not shown any change in the bioavailability of ofloxacin in infectious disease patients versus normal volunteers (1,2,6,7,11,13,14). The bioavailability of ofloxacin has been previously investigated after administration of single doses (5,15), but to our knowledge this is the first study that has investigated it under steady-state conditions.…”
Section: Methodsmentioning
confidence: 88%
“…The subjects were judged healthy on the basis of the results of the prestudy values of vital signs (pulse, oral temperature, and sitting blood pressure), laboratory profiles (hematology profile, blood chemistry, and urinalysis), urine toxicology screen, and human immunodeficiency virus screen. None of the subjects had a previous history of allergy to 2 h of a dose. For the morning doses, subjects fasted from at least midnight of the previous day.…”
Section: Methodsmentioning
confidence: 99%